(untitled) (Journal of Asian Development Studies, 2026)
Digital transformation remains challenging for small and medium-sized enterprises (SMEs), particularly in the developing world where resource and skill limitations hinder technology adoption. This study investigates the connection of digital skills with digital transformation within SMEs sector in Pakistan, with perceived usefulness as a mediator and competitive pressure as a moderator. It integrates the Resource-Based View and Technology Acceptance Model to propose and examine a moderated mediation model using a sample of 439 SME owner-managers. SPSS and SmartPLS software were employed for descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM) respectively. Findings show that digital skills have a significant effect on digital transformation adoption (β = 0.34, p < 0.001) and perceived usefulness (β = 0.56, p < 0.001), and perceived usefulness positively impacts adoption (β = 0.29, p < 0.001). Mediation results verify a significant indirect impact of digital skills via perceived usefulness (β = 0.16, p < 0.001), suggesting partial mediation. Furthermore, competitive pressure moderates the effect of digital skills on adoption (β = 0.12, p = 0.004), enhancing this effect with greater competition. In conclusion, the results reveal that digital transformation in SMEs is influenced by internal skills, cognitive appraisal and competitive pressure, with perceived usefulness playing a pivotal role in translating digital skills into adoption.